Hepatocellular Bile Salt Transport: Lessons from Cholestasis - Michael Trauner; Peter Fickert; Rudolf E Stauber (Canadian Journal of Gastroenterology)
Hepatic uptake and excretion of bile salts and several nonbile salt organic anions (eg, bilirubin) are mediated by a distinct set of polarized transport systems at the basolateral and apical plasma membrane domains of hepatocytes and bile duct epithelial cells (cholangiocytes). With the increasing availability of molecular probes for these transporters, evidence now exists that decreased or even absent expression of hepatobiliary transport proteins in hepatocytes or cholangiocytes may explain impaired transport function that results in hyperbilirubinemia and cholestasis. This review summarizes the molecular defects in hepatocellular membrane transporters that are associated with hereditary and acquired forms of cholestatic liver disease.